Production process for preparing electrolytic cobalt by adopting sulfuric acid wet method
Through the sulfuric acid wet process, using anhydrous ethanol and mixed extractant, combined with electrolytic treatment, the problems of high energy consumption, heavy pollution and low recovery rate of the traditional cobalt production process were successfully solved, and efficient and environmentally friendly cobalt recycling and purification were achieved.
Patent Information
- Application Number
- CN202411693009.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional cobalt production processes have problems such as high energy consumption, heavy pollution and low recovery rate, and my country's cobalt resources are relatively scarce, resulting in difficulty in supplying cobalt raw materials.
Electrolytic cobalt is prepared by using the sulfuric acid wet process. After crushing and sieving the cobalt slag, it is placed in the sulfuric acid solution and added anhydrous ethanol for water bath stirring. Then the pH value is adjusted, air is introduced for ventilation, and extraction is carried out with mixed extraction agent. , and finally electrolytic cobalt is obtained by electrolytic treatment.
This process significantly improves the recycling efficiency and purity of cobalt, reduces energy consumption and pollution, meets the requirements of modern green production, and is clean, environmentally friendly, simple and efficient.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrometallurgy and relates to a production process for preparing electrolytic cobalt by a sulfuric acid hydroprocess. Background Art
[0002] Cobalt has excellent properties such as high strength, heat resistance and strong magnetism, and is an important strategic resource. It is an important additive in superalloys and alloy steels, and is also widely used in aviation, battery functional materials and chemical industrial products. At present, with the accelerated pace of industrialization and urbanization in the world, energy is becoming increasingly scarce, and the use of batteries is becoming more and more extensive. Cobalt is an important metal in batteries, and it is expected that the development and utilization of cobalt resources will reach a new climax in the future. However, my country's cobalt resources are relatively scarce, making it difficult to supply cobalt raw materials. In addition, the traditional cobalt production process has problems such as high energy consumption, heavy pollution and low recovery rate. Therefore, the development of efficient and environmentally friendly cobalt production processes has become the focus of industry attention. Summary of the invention
[0003] The object of the present invention is to provide a production process for preparing electrolytic cobalt by a sulfuric acid wet method, which has the characteristics of being clean, environmentally friendly, simple and efficient.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A production process for preparing electrolytic cobalt by a sulfuric acid wet process, wherein the specific process of the production process for preparing electrolytic cobalt by a sulfuric acid wet process is as follows:
[0006] S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag;
[0007] S2: placing the refined cobalt slag in a sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate;
[0008] S3: adjusting the pH of the leaching solution to 4, passing air into the leaching solution for 3 hours at a temperature of 25°C, and filtering to obtain a purified leaching solution;
[0009] S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, the pH of the extraction system is adjusted to 4-6 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 50-70°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase;
[0010] S5: using 2M hydrochloric acid to strip the cobalt-containing organic phase, adjusting the pH of the stripping system to 3, the stripping temperature to 37° C., and the stripping time to 15 min to obtain a raffinate;
[0011] S6: electrolyzing the raffinate, adding 2wt% boric acid buffer, the electrolysis temperature is 55°C, the electrolysis time is 6h, washing the electrolytic cobalt with deionized water for multiple times, and drying it in a constant temperature drying oven at 60°C for 12h to obtain the electrolytic cobalt.
[0012] Furthermore, the components of the cobalt slag in S1 are cobalt, zinc, cadmium, iron, lead and nickel.
[0013] Furthermore, the concentration of the sulfuric acid solution in S2 is 3M.
[0014] Furthermore, the air intake flow rate in S3 is 8 L / min.
[0015] Furthermore, the mixed extractant in S4 is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:2.
[0016] Furthermore, the volume ratio of the hydrochloric acid solution to the cobalt-containing organic phase in S5 is 4:1.
[0017] Furthermore, in the S6, the anode is a platinum electrode and the cathode is a pure cobalt sheet.
[0018] Furthermore, the current density in S6 is 300A / m 2 , the cell voltage is 2V.
[0019] As an effective reducing agent, ethanol can participate in the leaching process and reduce high-valent cobalt ions to low-valent cobalt ions through electron transfer. This process not only accelerates the dissolution of cobalt from the solid phase to the liquid phase, but also significantly improves the recovery efficiency of cobalt. The high water solubility of ethanol is a key factor in its ability to widely contact and effectively act on the surface of transition metal oxides. Through its intermolecular interactions, ethanol can penetrate into the oxide surface and promote the electron exchange between high-valent metal ions and reducing agents, thereby achieving the reduction and dissolution of metal ions. One of the oxidation products of ethanol is acetic acid, which also has good water solubility and dissociates into H + , which helps to lower the pH of the solution and further promote the acid hydrolysis process of metal oxides, thereby enhancing the recovery effect. In addition, ethanol is usually made by fermenting starch commonly found in foods such as corn, wheat, and potatoes, or by directly hydrating ethylene from the petroleum industry. Compared with some traditional reducing agents, it has significant environmental advantages.
[0020] When the pH value of the solution is about 4, Fe 3+The hydrolysis precipitation potential of oxygen is significantly reduced, and the iron ions are more likely to precipitate in the form of iron hydroxide. The standard electrode potential of oxygen is much higher than that of Fe 3+ / Fe 2+ Therefore, in the presence of Fe 2+ Air is introduced into the solution. The oxygen in the air can act as a strong oxidant to convert Fe 2+ Oxidized to Fe 3+ Since the solution pH has been adjusted to 4, the newly generated Fe 3+ It will quickly hydrolyze and form iron hydroxide precipitation. This process not only effectively removes iron impurities in the solution, but also greatly reduces the energy consumption required in the purification process by using oxygen in the air as an oxidant, achieving a green and economical purification effect.
[0021] As an efficient metal extractant, Cyanex 272 has a unique chemical structure that promotes the selective binding of cobalt and nickel metal ions. When Cyanex 272 is used in combination with tributyl phosphate, the two exhibit a significant synergistic effect in the extraction process. The specific functional groups of Cyanex 272 interact with the molecular structure of tributyl phosphate to form a composite extraction environment with a higher affinity for cobalt ions, which effectively reduces the interference of impurity ions and achieves high-purity extraction of cobalt ions. This mixed extraction system not only improves the selective extraction ability of cobalt ions, but also further enhances the extraction efficiency by optimizing the extraction conditions. The fine control of the extraction conditions ensures that the extraction process reaches an efficient balance in a relatively short time, thereby improving the overall production efficiency. The mixed application of Cyanex 272 and tributyl phosphate in kerosene constitutes a relatively mild and environmentally friendly extraction system. Compared with traditional extraction methods that may produce harmful byproducts, this system significantly reduces the risk of environmental pollution and meets the requirements of modern industry for green production.
[0022] Beneficial effects of the present invention:
[0023] (1) Using ethanol as a reducing agent, through its high water solubility and electron transfer ability, it accelerates the reduction process of cobalt ions from high valence state to low valence state, significantly improving the dissolution rate and recovery efficiency of cobalt from solid phase to liquid phase. At the same time, acetic acid, the oxidation product of ethanol, helps to adjust the pH value of the solution, further promotes the acidolysis of metal oxides, and enhances the recovery effect. In addition, compared with traditional reducing agents, ethanol shows more significant environmental advantages.
[0024] (2) The mixed use of Cyanex 272 and tributyl phosphate, with its unique chemical structure and synergistic effect, improves the selective extraction ability of cobalt ions, reduces impurity interference, and achieves rapid and efficient extraction of high-purity cobalt ions. This mixed extraction system not only improves production efficiency, but also significantly reduces the risk of environmental pollution due to its mild and environmentally friendly characteristics, meeting the needs of modern green production. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] CAS / Article No. Manufacturer Cyanex272 83411-71-6 Changshu Xinte Chemical Co., Ltd. Tributyl phosphate 126-73-8 Wuxi Donghu Chemical Plant kerosene 8008-20-6 Shanghai Aladdin Biochemical Technology Co., Ltd. Boric acid buffer B885512 Shanghai MacLean Biochemical Technology Co., Ltd. Anhydrous ethanol 64-17-5 Changshu Hongsheng Fine Chemical Co., Ltd. Sodium hydroxide 1310-73-2 Shandong Zhongyuan Chemical Co., Ltd. hydrochloric acid 7647-01-0 Shanghai Aladdin Biochemical Technology Co., Ltd.
[0027] The composition of the cobalt slag is, by mass percentage, 5.5% cobalt, 12.2% zinc, 4.4% cadmium, 3.2% iron, 0.6% lead and 0.3% nickel.
[0028] Example 1
[0029] S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag;
[0030] S2: placing the refined cobalt slag in a 3M sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate;
[0031] S3: adjusting the pH of the leachate to 4, passing air into the leachate at an air flow rate of 8 L / min, aeration time of 3 h, and a temperature of 25°C, and filtering to obtain a purified leachate;
[0032] S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, wherein the mixed extractant is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:2, the pH of the extraction system is adjusted to 4 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 50°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase;
[0033] S5: using 2M hydrochloric acid to back-extract the cobalt-containing organic phase, the volume ratio of the 2M hydrochloric acid solution to the cobalt-containing organic phase is 4:1, the pH in the back-extraction system is adjusted to 3, the back-extraction temperature is 37° C., the back-extraction time is 15 min, and a raffinate is obtained;
[0034] S6: The raffinate is electrolyzed, the anode is a platinum electrode, the cathode is a pure cobalt sheet, 2wt% boric acid buffer is added, the electrolysis temperature is 55°C, the electrolysis time is 6h, and the current density is 300A / m 2 , the cell voltage is 2V, the cobalt obtained by electrolysis is washed multiple times with deionized water, and placed in a constant temperature drying oven at 60°C for 12 hours to obtain the electrolytic cobalt.
[0035] Example 2
[0036] S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag;
[0037] S2: placing the refined cobalt slag in a 3M sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate;
[0038] S3: adjusting the pH of the leachate to 4, passing air into the leachate at an air flow rate of 8 L / min, aeration time of 3 h, and a temperature of 25°C, and filtering to obtain a purified leachate;
[0039] S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, wherein the mixed extractant is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:2, the pH of the extraction system is adjusted to 5 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 50°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase;
[0040] S5: using 2M hydrochloric acid to back-extract the cobalt-containing organic phase, the volume ratio of the 2M hydrochloric acid solution to the cobalt-containing organic phase is 4:1, the pH in the back-extraction system is adjusted to 3, the back-extraction temperature is 37° C., the back-extraction time is 15 min, and a raffinate is obtained;
[0041] S6: The raffinate is electrolyzed, the anode is a platinum electrode, the cathode is a pure cobalt sheet, 2wt% boric acid buffer is added, the electrolysis temperature is 55°C, the electrolysis time is 6h, and the current density is 300A / m 2 , the cell voltage is 2V, the cobalt obtained by electrolysis is washed multiple times with deionized water, and placed in a constant temperature drying oven at 60°C for 12 hours to obtain the electrolytic cobalt.
[0042] Example 3
[0043] S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag;
[0044] S2: placing the refined cobalt slag in a 3M sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate;
[0045] S3: adjusting the pH of the leachate to 4, passing air into the leachate at an air flow rate of 8 L / min, aeration time of 3 h, and a temperature of 25°C, and filtering to obtain a purified leachate;
[0046] S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, wherein the mixed extractant is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:2, the pH of the extraction system is adjusted to 6 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 50°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase;
[0047] S5: using 2M hydrochloric acid to back-extract the cobalt-containing organic phase, the volume ratio of the 2M hydrochloric acid solution to the cobalt-containing organic phase is 4:1, the pH in the back-extraction system is adjusted to 3, the back-extraction temperature is 37° C., the back-extraction time is 15 min, and a raffinate is obtained;
[0048] S6: The raffinate is electrolyzed, the anode is a platinum electrode, the cathode is a pure cobalt sheet, 2wt% boric acid buffer is added, the electrolysis temperature is 55°C, the electrolysis time is 6h, and the current density is 300A / m 2 , the cell voltage is 2V, the cobalt obtained by electrolysis is washed multiple times with deionized water, and placed in a constant temperature drying oven at 60°C for 12 hours to obtain the electrolytic cobalt.
[0049] Example 4
[0050] S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag;
[0051] S2: placing the refined cobalt slag in a 3M sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate;
[0052] S3: adjusting the pH of the leachate to 4, passing air into the leachate at an air flow rate of 8 L / min, aeration time of 3 h, and a temperature of 25°C, and filtering to obtain a purified leachate;
[0053] S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, wherein the mixed extractant is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:2, the pH of the extraction system is adjusted to 4 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 60°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase;
[0054] S5: using 2M hydrochloric acid to back-extract the cobalt-containing organic phase, the volume ratio of the 2M hydrochloric acid solution to the cobalt-containing organic phase is 4:1, the pH in the back-extraction system is adjusted to 3, the back-extraction temperature is 37° C., the back-extraction time is 15 min, and a raffinate is obtained;
[0055] S6: The raffinate is electrolyzed, the anode is a platinum electrode, the cathode is a pure cobalt sheet, 2wt% boric acid buffer is added, the electrolysis temperature is 55°C, the electrolysis time is 6h, and the current density is 300A / m 2 , the cell voltage is 2V, the cobalt obtained by electrolysis is washed multiple times with deionized water, and placed in a constant temperature drying oven at 60°C for 12 hours to obtain the electrolytic cobalt.
[0056] Example 5
[0057] S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag;
[0058] S2: placing the refined cobalt slag in a 3M sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate;
[0059] S3: adjusting the pH of the leachate to 4, passing air into the leachate at an air flow rate of 8 L / min, aeration time of 3 h, and a temperature of 25°C, and filtering to obtain a purified leachate;
[0060] S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, wherein the mixed extractant is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:2, the pH of the extraction system is adjusted to 4 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 70°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase;
[0061] S5: using 2M hydrochloric acid to back-extract the cobalt-containing organic phase, the volume ratio of the 2M hydrochloric acid solution to the cobalt-containing organic phase is 4:1, the pH in the back-extraction system is adjusted to 3, the back-extraction temperature is 37° C., the back-extraction time is 15 min, and a raffinate is obtained;
[0062] S6: The raffinate is electrolyzed, the anode is a platinum electrode, the cathode is a pure cobalt sheet, 2wt% boric acid buffer is added, the electrolysis temperature is 55°C, the electrolysis time is 6h, and the current density is 300A / m 2 , the cell voltage is 2V, the cobalt obtained by electrolysis is washed multiple times with deionized water, and placed in a constant temperature drying oven at 60°C for 12 hours to obtain the electrolytic cobalt.
[0063] Comparative Example 1
[0064] No anhydrous ethanol was added during the acid leaching process, and the remaining steps were consistent with those in Example 1.
[0065] Comparative Example 2
[0066] The extractant is composed of Cyanex 272 and kerosene in a volume ratio of 1:1, and the remaining steps are consistent with Example 1.
[0067] Comparative Example 3
[0068] The extractant is composed of tributyl phosphate and kerosene in a volume ratio of 1:1, and the remaining steps are consistent with Example 1.
[0069] The purity of the electrolytic cobalt prepared in the embodiment and the comparative example was analyzed by inductively coupled plasma mass spectrometry. The experimental results are summarized in the following table:
[0070] Electrolytic cobalt purity (%) Example 1 99.8 Example 2 99.1 Example 3 97.4 Example 4 99.9 Example 5 99.9 Comparative Example 1 97.8 Comparative Example 2 91.1 Comparative Example 3 89.6
[0071] It can be seen from the data of the embodiments and comparative examples that the mixed extractant has a better extraction effect when the pH is 4 and the temperature is 60°C or above; the introduction of anhydrous ethanol is beneficial to the efficiency of sulfuric acid leaching, and also has a certain influence on the purity of the final product; the mixed extractant prepared by compounding Cyanex 272, tributyl phosphate and kerosene in a certain volume ratio has a better ability to resist interference from impurity elements.
[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A production process for preparing electrolytic cobalt by a sulfuric acid wet method, characterized in that: The specific process of the production process of electrolytic cobalt prepared by the sulfuric acid wet method is as follows: S1: placing the cobalt slag in a crusher for crushing, and then screening the crushed cobalt slag with a 400-mesh screen to obtain refined cobalt slag; S2: placing the refined cobalt slag in a sulfuric acid solution, wherein the solid-liquid mass ratio of the refined cobalt slag to the sulfuric acid solution is 1:5, adding 5wt% anhydrous ethanol, stirring in a water bath at 60°C for 1h, and filtering to obtain a leachate; S3: adjusting the pH of the leaching solution to 4, passing air into the leaching solution for 3 hours at a temperature of 25°C, and filtering to obtain a purified leaching solution; S4: the purified leachate and the mixed extractant are mixed in a volume ratio of 1:1, the pH of the extraction system is adjusted to 4-6 using a 1M sulfuric acid solution or a 0.5M sodium hydroxide solution, the extraction temperature is 50-70°C, the extraction equilibrium time is 40min, and after standing for 10min, a separating funnel is used to separate the cobalt-containing organic phase and the aqueous phase; S5: using 2M hydrochloric acid to strip the cobalt-containing organic phase, adjusting the pH of the stripping system to 3, the stripping temperature to 37° C., and the stripping time to 15 min to obtain a raffinate; S6: electrolyzing the raffinate, adding 2wt% boric acid buffer, the electrolysis temperature is 55°C, the electrolysis time is 6h, washing the electrolytic cobalt with deionized water for multiple times, and drying it in a constant temperature drying oven at 60°C for 12h to obtain the electrolytic cobalt.
2. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The components of the cobalt slag in S1 are cobalt, zinc, cadmium, iron, lead and nickel.
3. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The concentration of the sulfuric acid solution in S2 is 3M.
4. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The air intake flow rate of the S3 is 8 L / min.
5. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The mixed extractant in S4 is composed of Cyanex 272, tributyl phosphate and kerosene in a volume ratio of 1:1:
2.
6. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The volume ratio of the hydrochloric acid solution to the cobalt-containing organic phase in S5 is 4:
1.
7. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The anode in S6 is a platinum electrode, and the cathode is a pure cobalt sheet.
8. The production process for preparing electrolytic cobalt by a sulfuric acid wet method according to claim 1, characterized in that: The current density in S6 is 300A / m 2 , the cell voltage is 2V.
Citation Information
Patent Citations
Method for preparing electric deposited cobalt
CN102330111A
Process for purifying cobalt by electro-depositing cobalt chloride solution through cyclone electrolysis technology and reclaiming residual chlorine
CN102808194A
Synergistic extraction and separation method for iron, cobalt and manganese ions in laterite-nickel ore leaching solution
CN109487080A
Method for recovering Co and Li in waste lithium battery by using ethanol as reductant through wet method
CN109706320A
Method for preparing cobalt ferrite from cobalt-containing slag
CN112410568A